Broken by War, Haunted by Memories: an Analysis of Trauma Experienced by Salama in Zoulfa Katouh’s as Long as the Lemon Trees Grow - Sephia Rahmawati; Anang Widodo (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2026)
The Syrian civil war, a bloody conflict sparked by popular rebellions against the government's rule, serves as the backdrop for Zoulfa Katouh's As Long as the Lemon Trees Grow. After being thrown into the harsh realities of war, the main character, Salama, a once-normal pharmacy student, is forced to take on the roles of surgeon and nurse amid the mayhem. She suffers from severe psychological trauma as a result of this sudden change and the atrocities of war. This study uses Cathy Caruth's trauma theory (2016) to analyze the causes, symptoms, and effects of Salama's trauma. Using a qualitative approach, the study entailed closely examining the novel, paying special attention to textual cues that disclose the protagonist's mental state. A detailed examination of Salama's traumatic experiences was made possible by the methodical categorization of key passages to answer the main research questions. The results show that the destruction caused by the civil war is the main source of Salama's trauma. Her ongoing negative thoughts, crippling hallucinations, and frequent flashbacks are some of the ways that her psychological distress shows up. Disrupted eating and sleep patterns, overwhelming guilt, and vivid visual hallucinations are all signs of the war's lasting effects on her mental health. Together, these symptoms show how trauma has a significant and complex impact on her mental health.